2020
DOI: 10.21203/rs.3.rs-41473/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of novel loci and candidate genes for cucumber downy mildew resistance using GWAS

Abstract: Background Downy mildew (DM) is one of the most serious diseases in cucumber and brings the loss of yield and profit. Multiple QTLs for DM resistance have been detected, however, no loci related to resistance was reported using genome-wide association analysis (GWAS). In this study, the core germplasm (CG) of cucumber lines that had been constructed and resequenced were used to identify DM resistance Loci using GWAS technology. Results Thirteen loci (dmG1.1, dmG1.2, dmG2.1, dmG2.2, dmG3.1, dmG4.1, dmG4.2, dm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In this CG population, a significant association between resistances to PM and DM was observed ( Supplementary Figure S2 ). We detected 13 loci for PM resistance in this study and 18 loci for DM resistance in our previous study [ 34 ]. A number of loci are colocalized, including pmG1.1 and dmG1.1 , pmG2.2 and dmG2.2 , pmG5.2 , and dmG5.1 , as well as pmG5.3 and dmG5.2 ( Figure 11 ).…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…In this CG population, a significant association between resistances to PM and DM was observed ( Supplementary Figure S2 ). We detected 13 loci for PM resistance in this study and 18 loci for DM resistance in our previous study [ 34 ]. A number of loci are colocalized, including pmG1.1 and dmG1.1 , pmG2.2 and dmG2.2 , pmG5.2 , and dmG5.1 , as well as pmG5.3 and dmG5.2 ( Figure 11 ).…”
Section: Discussionsupporting
confidence: 60%
“…In order to verify the potential link between these S genes and the QTLs, we analyzed the effect of SNPs in these S genes on PM DI of the CG lines. We also included the DM data of this CG population in our previous study [ 34 ] since it has been often reported that resistance to PM and DM is linked in cucumber [ 21 ], which is supported by the significant correlation between the DIs of PM and DM in this CG population ( Supplementary Figure S2 ). Based on the SNPs variation in the PMR genes ( Supplementary File S6 ), only SNPs in CsaPMR6-10 showed a significant difference on DI of PM (the average of spring 2013, spring 2014, and autumn 2014), but not on DI of DM (the average of spring 2014, autumn 2014, and autumn 2015) ( Figure 10 a).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations